2019
DOI: 10.1177/0706743719889551
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Mental Health Following Exposure to Positive and Harsh Parenting in Childhood

Abstract: Objectives: The purpose of the present study was to assess longitudinal associations between positive and harsh parenting in childhood and adolescent mental and behavioral difficulties. Methods: Data were drawn from Canada’s population-based National Longitudinal Survey of Children and Youth (data collected from 1994 to 2009, analyzed 2018). The sample included 9,882 adolescents aged 12/13 years old. Parents self-reported positive and harsh parenting when children were 6/7, 8/9, and 10/11 years old. Symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
1
27
0
2
Order By: Relevance
“…For example, child misbehavior may elicit more harsh disciplinary techniques in an attempt to control behavior (Reitz et al, 2006). However, in recent study using NLSCY data, we found that parenting behavior in childhood predicted adolescent mental illness even after adjusting for baseline symptoms (Kingsbury et al, 2019). Our study assessed parenting of the primary caregiver—most often the mother.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…For example, child misbehavior may elicit more harsh disciplinary techniques in an attempt to control behavior (Reitz et al, 2006). However, in recent study using NLSCY data, we found that parenting behavior in childhood predicted adolescent mental illness even after adjusting for baseline symptoms (Kingsbury et al, 2019). Our study assessed parenting of the primary caregiver—most often the mother.…”
Section: Discussionmentioning
confidence: 68%
“…How a parent chooses to discipline a child can influence emotional and behavioral development, and mental health. For example, the use of harsh disciplinary practices such as yelling or hitting a child has been associated with subsequent increased risk of depression, hyperactivity, and aggression in adolescence, particularly among boys (Kingsbury et al, 2019). Authoritarian parenting and harsh disciplinary practices are also associated with higher risk of suicidal thought and suicide attempt (Donath et al, 2014; Lai & McBride‐Chang, 2001; Xing et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under negative parenting, corporal punishment was seen to be significantly higher compared to previous literature. Kingsbury et al (2019) emphasize the role of harsh parenting in the development of both internalizing and externalizing disorders.…”
Section: Parenting Practicesmentioning
confidence: 99%
“…Harsh parenting (HP) includes coercive parenting tactics ranging from mild corporal punishment to escalated physical abuse and cruelty [3]. HP is associated with child aggression [4] [5] [6], lower verbal skills [7], problem behaviors [7] [8] [9], and depression [10], which have long-term effects on children's mental health. By breaking the cycle of violence in parenting, we can contribute to the prevention of mental illness and the improvement of lifelong mental health.…”
Section: Introductionmentioning
confidence: 99%